Effects of Moringa Oliefera on Thickness of Tunica Intima and Tunica Media In Aorta of Diabetic Rat - Razzaq, Mehwish; Hamid, Shabnam; Razzaq, Sehrish; Aamir, Muhammad Omer; Sana, Fatima; Abaid, Mehwish (Pakistan Armed Forces Medical Journal, 2025)
Objective: To study the effects of Moringa Oliefera on thickness of Tunica intima and media in aorta of Streptozotocin induced diabetic rat. Study Design: Laboratory-Based Experimental Study. Place and Duration of Study: Army Medical College Rawalpindi, Pakistan and National Institute of Health Islamabad, Pakistan from Jun to Dec 2020. Methodology: Ninety Sprague Dawley rats were randomly divided into a control group A, and two experimental groups B and C, each consisting of thirty rats. In both experimental groups High fat diet was given, diabetes mellitus was induced by injecting Streptozotocin at a dose of 35mg/kg body weight. Aqueous extract of Moringa Oliefera leaves at a dose of 200 mg/kg body weight was administered orally for 8 weeks to experimental Group-C. The animals were sacrificed at the end of experiment, aorta dissected out, fixed and stained with Elastin Von Geison (EVG) for histological analysis. Thickness of Tunica Intima and Tunica Media were measured on histological slides using image J software. Results: Thickness of Intima of rat aorta in experimental Group-C was significantly less than Group-B but more than control Group A. Similarly, in intergroup comparison difference in mean thickness of tunica media of rat aorta in experimental Group-C was much less than Group-B but more than control Group A. Conclusion: Moringa Oliefera has ameliorative effects against diabetes induced increase in tunica intima and media thickness.